Singularity theory and forced symmetry breaking in equations - Furter, Jacques-Eli; Ruas, Maria Aparecida Soare; Sitta, Angela Maria [UNESP] (Universitat Autonoma de Barcelona, 2010)
A theory of bifurcation equivalence for forced symmetry breaking bifurcation problems is developed. We classify (O(2), 1) problems of corank 2 of low codimension and discuss examples of bifurcation problems leading to such symmetry breaking. © 2009 Departament de Matemàtiques Universitat Autònoma de Barcelona.